The Adolescent's Competency for Interacting with Alcohol as a Determinant of Intake: The Role of Self-Regulation - de la Fuente, Jesús; Cubero, Inmaculada; Sánchez-Amate, Mari Carmen; Peralta, Francisco J.; Garzón, Angélica; Fiz Pérez, Javier (Frontiers in Psychology, 2017)
The competency for interacting with alcohol is a highly useful Educational Psychology model for preventing and for understanding the different behavioral levels of this interaction. Knowledge of facts, concepts and principles about alcohol use, self-regulated behavior, and attitudes toward alcohol are predictive of adequate interaction with alcohol. The objective of this study was to empirically evaluate this postulated relationship. A total of 328 Spanish adolescents participated, between the ages of 12 and 17. All were enrolled in 1st–4th year of compulsory secondary education, in the context of the ALADO Program for prevention of alcohol intake in adolescents. An ex post facto design was used, with inferential analyses and SEM analyses. Results show an interdependence relationship, with significant structural prediction between the behavioral levels defined and the level of alcohol intake, with principles, self-regulating control and attitudes carrying more weight. Analyses are presented, as are implications for psychoeducational intervention using preventive programs based on this competency model.